PENGARUH PEMBERIAN UMPAN BALIK DAN MOTIVASI BERPRESTASI TERHADAP HASIL BELAJAR SISWA - Pujiati, Pujiati; Nurdin, Nurdin; Kusuma, Wayan Andi (JEE (Jurnal Edukasi Ekobis), 2015)
The problem in this study is the low learning achievement of economy class X students of SMA Negeri 1 Candipuro semester grade academic year 2013/2014. The purpose of this study was to determine the effect of providing feedback and achievement motivation on learning achievement of economy class X students of SMA Negeri 1 Candipuro in odd semester academic year of 2013/2014. The population in this study is the first semester of class X students of SMA Negeri 1 Candipuro much as 3 classes with a total number of 90 students. Sampling using non-probability sampling with sampling saturated type, number of samples obtained population is 90 people. Based on the analysis, it obtained the following results: (1) there is effect of feedback on learning outcomes economy, (2) there is effect of achievement motivation on learning outcomes of the semester economics, (3) there is a feedback effect of achievement motivation on learning outcomes economy of students. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian umpan balik dan motivasi berprestasi terhadap hasil belajar ekonomi siswa kelas X semester ganjil SMA Negeri 1 Candipuro Tahun Pelajaran 2013/2014. Populasi dalam penelitian ini adalah siswa kelas X semester ganjil SMA Negeri 1 Candipuro sebanyak 3 kelas dengan jumlah siswa keseluruhan 90 orang. Penarikan sampel menggunakan non probability sampling dengan jenis sampling jenuh, didapat sampel sebanyak jumlah populasi yaitu 90 orang. Berdasarkan analisis diperoleh hasil penelitian sebagai berikut : (1) ada pengaruh pemberian umpan balik terhadap hasil belajar ekonomi siswa, (2) ada pengaruh motivasi berprestasi terhadap hasil belajar ekonomi siswa, (3) ada pengaruh pemberian umpan balik dan motivasi berprestasi terhadap hasil belajar ekonomi siswa.Kata kunci: hasil belajar, motivasi berprestasi, pemberian umpan balik